A Survey of Primary Health Care Provision at a Forward Operating Base in Afghanistan During Operation HERRICK 10. Issue 2 (1st June 2011) - Hawksley, O J; Jeyanathan, J; Mears, K; Simpson, R
Abstract : Objectives: To record and discuss patient morbidity treated in a Forward Operating Base in Afghanistan and explore who delivers the care. Methods: Prospective case series of all patients presenting to the Regimental Aid Post during a summer tour of Afghanistan. Results: 1903 episodes of care were delivered over a 6-month period in 2009. Afghan patients represented 32.8% of all cases seen. The majority of cases were related to primary care. The most common types of presentations were dermatological, other general medical conditions, other injuries and disorders of the digestive tract. Combat Medical Technicians (CMT) were able to deal with 47% of all cases using the CMT protocols. Conclusions: Primary care in forward areas involves patients from a spectrum of backgrounds with multiple morbidities and diagnoses. Consideration should be given for further research into the area of the consultation at the front line to aid patient care. Combat Medical Technicians were able to treat nearly 50% of all cases by themselves but this left a significant number where the assistance of a Medical Officer was required. Consideration should be given for further research into preparation of Combat Medical Technicians for autonomous working at the front line.